Sistem Informasi Geografis Persebaran Pendidikan, Rumah Sakit, dan Industri Kabupaten Demak Memanfaatkan gis.co.id - Jefri Firmansyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the distribution of education, hospitals, and industries in Demak Regency, Central Java, Indonesia. The study used a descriptive quantitative approach with spatial analysis techniques. Data were collected from the Central Statistics Agency (BPS) of Demak Regency. The results showed that the distribution of education, hospitals, and industries in Demak Regency is uneven. The majority of educational facilities are concentrated in the central and southern parts of the regency, while hospitals are mostly located in the central and northern parts. Meanwhile, industries are concentrated in the central and eastern parts of the regency. This uneven distribution can cause disparities in access to education, health services, and employment opportunities for the population of Demak Regency.